In bilico tra densità e diffusione: Atene, evoluzione urbana e società, all’ombra della crisi - Salvati, Luca (Scienze del Territorio, 2015)
As part of the debate on sustainable urban forms, the present study focuses on the possible interpretative keys of urban expansion processes which involved Athens, taken as an example of the development of Mediterranean cities. The study develops a reflection on the economic transformations and major social-demographic changes shown at an urban and regional level as possible determinants of the progressive shift in urban form. The discussion, reconnecting local and regional dynamics in a multi-disciplinary perspective, debates on Athens’ future development as a paradigmatic example for other Mediterranean cities, suspended in-between growth and crisis, anxiety for tomorrow and unceasing seek for past.